2022
DOI: 10.3390/su15010625
|View full text |Cite
|
Sign up to set email alerts
|

Soil–Plant–Microbe Interactions Determine Soil Biological Fertility by Altering Rhizospheric Nutrient Cycling and Biocrust Formation

Abstract: Understanding soil–plant–microbe inter- and intra- interactions are essential for ensuring proper soil health, quality, and soil-mediated ecosystem services (e.g., nutrient cycling) required for human–plant–animal life. Intensive and unsustainable farming practices can decrease soil microbial biodiversity, fertility, and quality leading to soil degradation, impaired nutrient cycling, and the incapability of soil to support plant growth. Under such a context, soil biological fertility can appear as a regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 242 publications
0
9
0
Order By: Relevance
“…However, the proper functioning of soil microbial communities depends on many factors including the availability of nutrients, temperature, water, soil structure, pH, and host genotypes and their secreted root exudates (Zgadzaj et al, 2016;Li et al, 2017;Pramanik et al, 2020;Vaidya and Stinchcombe, 2020). An understanding of endophytic or epiphytic soilmicrobe interactions with host roots is of great importance because of their potential to promote plant growth in various ways through enhanced nutrient, mineral and water use efficiency, increased production of phytohormones, induced biotic and abiotic stress tolerance, and minimized toxicity of contaminants (Bacon and White, 2016;Kumar et al, 2017;Harman and Uphoff, 2019;Bhattacharyya and Furtak, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the proper functioning of soil microbial communities depends on many factors including the availability of nutrients, temperature, water, soil structure, pH, and host genotypes and their secreted root exudates (Zgadzaj et al, 2016;Li et al, 2017;Pramanik et al, 2020;Vaidya and Stinchcombe, 2020). An understanding of endophytic or epiphytic soilmicrobe interactions with host roots is of great importance because of their potential to promote plant growth in various ways through enhanced nutrient, mineral and water use efficiency, increased production of phytohormones, induced biotic and abiotic stress tolerance, and minimized toxicity of contaminants (Bacon and White, 2016;Kumar et al, 2017;Harman and Uphoff, 2019;Bhattacharyya and Furtak, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The shift in dominance bacteria changes competition and cooperation between species in the bacterial community, impacting the complexity and stability of the bacterial network ( De Vries et al, 2018 ). Additionally, the rhizosphere regulates microbe-facilitated soil processes and services ( Bhattacharyya and Furtak, 2023 ), with plant root-associated secretions playing a key role in the rhizosphere by affecting the growth of microorganisms ( Fan et al, 2017 ). Moreover, previous studies have indicated that biological soil crust has the ability to produce extracellular polysaccharides secreted by filamentous cyanobacteria ( Belnap et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The soil nitrogen transformation process is mainly affected by soil enzyme activities and the differences in soil microbial communities [37]. The depolymerization process of nitrogen-containing polymers through the involvement of soil enzymes indirectly reflects the soil inorganic nitrogen supply capacity, regulates the soil nitrogen transformation intensity, and increases the soil nitrogen holding rate [13], which is of great significance for maintaining soil fertility and plant growth and development [40]. Optimizing nitrogen management under different rotation conditions is key to improving grain crop yields.…”
Section: Soil Quick-acting Nitrogen Contentmentioning
confidence: 99%